Telaah Surat As-Shaffat Ayat 79 Sebagai Do'a Perlindungan Dari Makhluk Berbisa: (Studi Living Qur'an Pada masyarakat Kampung Purwaraja, Desa Purwaraja, Kecamatan Menes) - Wahyudin; Syafi’in Mansur; Mus’idul Millah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This research aims to analyze the interpretation and practice of Surah As-Shaffat Verse 79 as a prayer for protection against venomous creatures among the people of Purwaraja Village. Using the Living Qur’an approach, this study examines how the verse is understood, transmitted, and practiced, as well as its benefits in daily life. The qualitative method employed includes observation, interviews, and literature review. The findings reveal that the people of Kampung Purwaraja believe Surah As-Shaffat Verse 79 serves as a protective prayer against the danger of venomous animals. This practice has been passed down orally through generations and taught by religious leaders. The community’s belief stems from the story of Prophet Noah, who saved animals during the great flood, which is interpreted as a metaphor for divine protection. The prayer is commonly recited before entering forests, working in gardens, or in situations that involve the risk of venomous animal encounters. Some community members report personal experiences of being protected after reciting the prayer, which reinforces their collective belief in its efficacy.